A nucleation rate limited model for grain boundary creep. (1st March 2023) - Dillon, Shen J.; Lang, Eric; Finkeldei, Sarah C.; Ouyang, Jia-hu; Hattar, Khalid
Abstract: The motion of grain boundary (GB) dislocations, via a combination of glide and climb, mediates GB plasticity during processes such as creep and GB stress relaxation. Creep within the low stress regime, where non-Newtonian GB creep occurs, remains poorly understood. Models for GB dislocation nucleation rate limited creep, however, have not been sufficiently developed previously in the literature. Herein, a model for nucleation rate limited kinetics is developed and demonstrated to describe existing creep data reasonably well, using physically realistic materials properties as inputs to the model. Graphical Abstract: Image, graphical abstract